Pengaruh Risiko Usaha Terhadap Profitabilitas Pada Lembaga Perkreditan Desa di Kecamatan Kuta Kabupaten Badung Periode 2010-2012 - Fahrizal, Fahrizal; Rahyuda, Henny (E-Jurnal Manajemen; Vol 3 No 10 (2014), 2014)
Profitability is the ability of banks to generate profit is effectively and efficiently. The expected level of corporate profitability, prone to risk. Risk is an event that will occur in the future, which can provide positive and negative results. Risk is managed by the company so that the company can withstand the impact of such risks. Credit risk, liquidity risk, and operational risk is the risk that often arise in the banking world. This research was conducted at the LPD in the District of Kuta Badung regency using saturated samples at 23 LPD residing in the District of Kuta Badung regency period 2010-2012. Linear regression analysis was data analysis in used of this research. Basedoon therresults of theaanalysis found thattcredit risk and operational risk significant negative effect on profitability, but liquidity risk significant positive effect on profitability. Key words: profitability, credit risk, liquidity risk, operational risk
Keywords: profitability, credit risk, liquidity risk, operational risk